From decimeter-scale elevated ionic conductivity regions in the cloud to lightning initiation - D. I. Iudin (Nature Portfolio, 2021)
Abstract In this work, we represent the lightning initiation scenario as a sequence of two transitions of discharge activity to progressively larger spatial scales: the first one is from small-scale avalanches to intermediate-scale streamers; and the second one is from streamers to the lightning seed. We postulate the existence of ion production centers in the cloud, whose occurrence is caused by electric field bursts accompanying hydrometeor collisions (or near collisions) in the turbulent thundercloud environment. When a new ion production center is created inside (fully or partially) the residual ion spot left behind by a previously established center, there is a cumulative effect in the increasing of ion concentration. As a result, the essentially non-conducting thundercloud becomes seeded by elevated ion-conductivity regions (EICRs) with spatial extent of 0.1–1 m and a lifetime of 1–10 s. The electric field on the surface of an EICR (due to its conductivity being at least 4 orders of magnitude higher than ambient) is a factor of 3 or more higher than ambient. For a maximum ambient electric field of 100 kV/m typically measured in thunderclouds, such field enhancement is sufficient for initiation of positive streamers and their propagation over distances of the order of decimeters, and this will be happening naturally, without any external agents (e.g., superenergetic cosmic ray particles) or extraordinary in-cloud conditions, such as very high potential differences or very large hydrometeors. Provided that each EICR generates at least one streamer during its lifetime, the streamers will form a 3D network, some parts of which will contain hot channel segments created via the cumulative heating and/or thermal-ionizational instability. These hot channel segments will polarize, interact with each other, and cluster, forming longer conducting structures in the cloud. When the ambient potential difference bridged by such a conducting structure exceeds 3 MV, we assume that the lightning seed, capable of self-sustained bidirectional extension, is formed.